Identification of Pharmacological Autophagy Regulators of Active Ulcerative Colitis - Qiu, Peishan; Liu, Lan; Fang, Jun; Zhang, Meng; Wang, Haizhou; Peng, Yanan; Chen, Min; Liu, Jing; Wang, Fan; Zhao, Qiu (Frontiers in Pharmacology, 2021)
Background: Ulcerative colitis (UC) is a chronic recurrent disease of unknown etiology. Recently, it has been reported that autophagy-related gene polymorphism is closely associated with increased risk of UC, and the therapeutic effect of some UC drugs is mediated by regulating autophagy pathways. This study aims to identify pivotal autophagy-related regulators in UC pathogenesis and provide novel molecular targets for the treatment of active UC. Methods: Gene expression profiles and clinical information of active UC patients were obtained from GEO databases. CIBERSORT was adopted to evaluate the immune cell infiltration. We used weighted gene co-expression network analysis (WGCNA) and differential expression analysis to identify the pivotal modules and genes associated with active UC. Subsequently, we conducted validation in the validation set and explored its relationship with commonly used UC therapeutics. Results: 36 healthy controls and 46 active UC patients have been obtained from the training set of GSE53306, GSE87466, and GSE134025. There were 423 differentially expressed genes (DEGs) found, which dramatically enriched in autophagy-related pathways. And more infiltration of mast cells, activated T cells, dendritic cells, and M1 macrophages were observed in the intestinal mucosa of active UC, while more infiltration of resting immune cells and M2 macrophages in healthy controls. WGCNA indicated that the turquoise and blue modules were the critical modules. CASP1, SERPINA1, and CCL2 have been identified as the hub autophagy-related genes of active UC, after combining DEGs and 232 autophagy-related genes from HADb with the genes of turquoise and blue modules, respectively. We further verified that CASP1, SERPINA1, and CCL2 were positively associated with active UC and served as an autophagy-related biomarker for active UC. Moreover, increased SERPINA1 in the involved intestinal mucosa was reduced in patients with active UC who responded to golimumab or glucocorticoid therapy. But, neither CASP1, SERPINA1, and CCL2 were changed by treatment of 5-aminosalicylic acid (5-ASA) and azathioprine. Conclusion: CASP1, SERPINA1, and CCL2 are autophagy-related hub genes of active UC. And SERPINA1 may serve as a new pharmacological autophagy regulator of UC, which provides a new target for the use of small molecules targeting autophagy in the treatment of active UC.